Characteristics of residential neighborhoods and their impact on the quality of life of residents in the suburb of Khalidiya in the Emirate of Sharjah: A social study - Alaqroubi, Hamda; Abouelkheir, Omaima (Al-Adab Journal, 2023)
The current study dealt with the characteristics of residential neighborhoods in the Emirate of Sharjah and their impact on the quality of life of the citizens residing in it through indicators of the residential environment and infrastructure, and indicators of service facilities available in it. Data and information were collected by relying on two main tools, which is the observation that the researcher is a resident of the suburb, and the in-depth interview guide, which was applied by conducting some interviews with members of the families of citizens residing in the suburb to identify their satisfaction with life in the suburb and their future aspirations. The results of the study concluded that(88%)of the respondents believed that the housing environment, infrastructure and service facilities greatly affected their quality of life, and this was shown through the results of the chi-square test, as the results indicated that there is a statistically significant relationship between housing ownership and considering it as one of the characteristics of The residential environment helped to raise the quality of life of the respondents in the suburb, while there was no statistically significant relationship between the sex variable and the consideration of the residential environment and infrastructure affected the quality of their lives, as all respondents, regardless of their gender, enjoy the characteristics of the suburb, while the service facilities index It was found that there is a statistically significant relationship between it and the age variable, as the younger individuals benefit from the educational and recreational facilities for their children more than the elderly.